Evaluation on Ambulance Design and Musculoskeletal Disorders Risk Factors among Ambulance Emergency Medical Service Personnel - Baba M. DEROS; Dian D.I. DARUIS; Sivadass THIRUCHELVAM; Rohayu OTHMAN; Dzulkarnain ISMAIL; Nor Faezah RABANI; Mohd F.M. HATTA; Amar HASSAN; Nur Iznie M. ZAKARIA (Tehran University of Medical Sciences, 2016)
Background: Injuries or pains occurred at various body's joints, ligaments, muscles, nerves, tendons, limbs, back and neck are classified as musculoskeletal disorders (MSDs). A single forceful exertion or repeated exposure to force, vibration or awkward posture can result in MSDs. This study was carried out by evaluating the relevant physical measurements of Class B ambulance used in Malaysia. The two main objectives of the study are to evaluate on the ambulance physical dimensions and workstation design and to conduct a Rapid Entire Body Assessment (REBA) to examine ambulance's emergency medical service (EMS) workers' activities and their associated MSDs risk factors. Methods: The two methodologies adopted for the study conducted in 2014 were direct measurement of the ambulance physical dimensions and workstation layout; and in-depth interviews of five EMS workers that provides patient care during transporting patient to a public hospital in Kota Bharu, Kelantan. REBA was conducted on seven commonly performed activities by EMS workers for identifying postural risks. Results: The study found ambulance width is too narrow and workstation layout may exposed EMS workers to MSDs risks. REBA scores for the seven commonly performed activities in the ambulance ranges from medium to very high.  Conclusion: Seven important MSDs risk factors to be considered in the design of the Class B ambulance for performing patient care activities that may lead towards EMS workers' injury are awkward posture, bumping, instability, narrow workspace dimension, inappropriate arrangement of storage cabinet, inappropriate arrangement of medical equipment, inadequate railing and seat, and inappropriate stretcher.   Keywords: Musculoskeletal disorders, Ambulance, EMS, Workers, REBA, Risks